A cost-efficient 61 GHz high-resolution radar sensor for industrial positioning and distance measurement - Wibbing, Sascha; Mann, Sebastian; Lurz, Fabian; Erhardt, Stefan; Lindner, Stefan; Weigel, Robert; Kölpin, Alexander (21st International Conference on Microwave, Radar and Wireless Communications (MIKON), 2016)
In this paper a novel 61GHz radar sensor node for industrial positioning and distance measurement is presented. The sensor provides numerous functions enabling a broad range of signal processing technologies and is designed with regard to cost-efficient implementation only using commercial available components without limiting the area of possible applications. Beside the requirement analysis and system design, several measurements of antenna isolation and distance resolution are depicted and discussed.
elib2cris::1512001600,wibbing2016a